2021
DOI: 10.1111/ijcp.14986
|View full text |Cite
|
Sign up to set email alerts
|

Serum LDH values in hypertensive disorders of pregnancy and their association with maternal and neonatal morbidity: A meta‐analysis

Abstract: Background Serum lactate dehydrogenase has been extensively studied in hypertensive disorders of pregnancy. However, to date, its clinical usefulness in the field remains unknown. The present meta‐analysis has been designed to evaluate differences in serum LDH values among patients with hypertensive disorders of pregnancy and to help determine its diagnostic accuracy as well its predictive accuracy in determining adverse pregnancy outcomes. Methods We searched Medline, Scopus, Clinicaltrials.gov, EMBASE, Cochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that serum lactate dehydrogenase (LDH), as a biochemical indicator for hypertension in pregnancy, has a sensitivity of 71% and a specificity of 74%. The average LDH level of patients with eclampsia is statistically higher than those with severe PE [42]. Therefore, LDH might have certain clinical significance in assessing the progress and severity of hypertension during pregnancy [43].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that serum lactate dehydrogenase (LDH), as a biochemical indicator for hypertension in pregnancy, has a sensitivity of 71% and a specificity of 74%. The average LDH level of patients with eclampsia is statistically higher than those with severe PE [42]. Therefore, LDH might have certain clinical significance in assessing the progress and severity of hypertension during pregnancy [43].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that LDH levels in the blood of PE patients are often significantly elevated, which may be related to vascular endothelial cell damage, tissue hypoxia and so on. Therefore, LDH test can be used as one of the blood biochemical indexes for PE patients in the acute stage ( 7 ). Uric acid (UA) is an indicator that is routinely measured in metabolic diseases such as nephropathy.…”
Section: Introductionmentioning
confidence: 99%